PENGARUH KEWAJIBAN PENYEDIAAN MODAL MINIMUM, RISIKO KREDIT, RISIKO PASAR, RISIKO OPERASIONAL DAN RISIKO LIKUIDITAS TERHADAP KINERJA KEUANGAN BANK - Ratih Nurmalita Hapsari (Parsimonia - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to examine from the effect of the Minimum Capital Adequacy Requirement, Credit Risk, Market Risk, Operational Risk, and Liquidity Risk on the Bank's Financial Performance. This study uses documentation techniques using secondary data from financial statements, this study uses 44 samples of companies listed on the Indonesia Stock Exchange in 2017–2019. In this study using multiple linear analysis using the Statistical Product and Service Solution (SPSS) test tool. The results of this study found that the Minimum Capital Adequacy Requirement (CAR) has no effect on financial performance, this is because banks have maintained and maintained capital stability as a result of regulations from Bank Indonesia and the Financial Services Authority related to capital aspects. Likewise, Liquidity Risk also has no effect on financial performance. This is in line with Agency Theory related to Agency Costs in the bank intermediation function, with results that do not affect it can be seen that bank management, supervisory institutions, even investors and customers have synergized in capital stability and liquidity so as not to incur other costs. The next result is Credit Risk which has a negative effect on the bank's financial performance, then Market Risk which has a positive effect on financial performance and Operational Risk has a negative effect on financial performance. Thus, it can be seen that the relationship with Signal Theory is that information that has an influence on bank performance can be a consideration for bank management in order to provide a good signal for related parties, especially investors and customers. The results of this study are also in line with the concept of Market Power Theory that bank management will always try to increase prices above marginal costs, so that it is expected to increase the profitability and performance of a bank.